Phrasemes and problem oriented approach - Lipavic Oštir, Alja (Verbum, 2020)
Studies as Jazbec & Enčeva (2012), Jazbec &Kacjan (2013) and Miletić (2018) show that although the didactic of phrasemes (Fleischer 1982, Lüger 1997, Hessky& Ettinger 1997) is pleading for a relevant, systematic, continuous and frequent use of phrasemes in German as a foreign language class, they appear predominantly at high levels of foreign language learning, only sporadically and often from the perspective of language comparison. The analysis of schoolbooks shows the presence of phrasemes which are often not appropriately didacticized and regarding data banks and vocabulary not always up-to date. In some recent studies (e.g. Hallsteinsdóttir 2016, Miletić 2018) we can find suggestions and models for the integration of phrasemes in German as a foreign language class, some with incorporation of multimodality. In this article we would like to consider the possibilities for the sensitization and receptive / productive acquisition of phrasemes as offered by the integration of a problem oriented approach in German as a foreign language class. We assume that the problem oriented approach is motivating and benefits transdisciplinary learning. The subject of this paper will be discussed based on some samples of different problem types (metalinguistic, intercultural and so-called non-linguistic problems). The so-called non-linguistic problems seem to be most appropriate because their concept is interdisciplinary, they foster motivation and in this type of problems phrasemes are not explicitly discussed, but appear in non-linguistic contexts to accomplish different non-linguistic goals, without neglecting the accomplishment of linguistic goals. As with the other types of problems, the non-linguistic problems should be adapted to the age of students and their cognitive development. Provided this criterion is fulfilled, the phrasemes appropriate to students’ age and cognitive development can also be included.